Spatial multiplexing gain in MIMO radars with widely separated antennas. Issue 2 (1st April 2018) - Nazari Majd, Mohammad; Radmard, Mojtaba; Chitgarha, Mohammad Mahdi; Farina, Alfonso; Bastani, Mohammad Hassan; Nayebi, Mohammad Mahdi
Abstract : Multiple‐input multiple‐output (MIMO) radars have attracted much attention for their superior ability to enhance a system's performance. In this study, the authors' goal was the study of the spatial multiplexing gain of MIMO radars with widely separated antennas (WS‐MIMO), which the authors showed that is equal to the number of unambiguously detectable targets. They obtained this number from two different aspects: first, by defining the ambiguity function of a WS‐MIMO radar in the case of multiple targets, suitable for such purpose; Second, by modelling the MIMO radar system with a MIMO wireless channel. They showed that a MIMO radar is indeed a MIMO wireless system communicating the information about the existence of the targets. By such modelling, they could easily make the relation between dual concepts of MIMO radar and MIMO communication, one of which is the multiplexing gain.